PENGARUH KUALITAS PRODUK DAN HARGA SERTA PROMOSI MELALUI MEDIA SOSIAL INSTAGRAM TERHADAP MINAT BELI PRODUK LAFY DI SAMARINDA - Widya Utami Putri; Lailatul hijrah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of product quality, price, and promotion through Instagram social media on purchase intention of Lafy products in Samarinda. The background of this research is based on the increasing competition in the beauty industry and the importance of marketing strategies in attracting consumer interest. The research method used is a quantitative approach with a survey technique using questionnaires. The sample consisted of 100 respondents selected using purposive sampling. Data were analyzed using validity and reliability tests, classical assumption tests, and multiple linear regression analysis. The results show that partially, product quality has a positive and significant effect on purchase intention with a significance value of 0.009, price has a positive and significant effect with a significance value of 0.007, and promotion through Instagram social media has the most dominant influence with a significance value of 0.000. Simultaneously, these variables significantly affect purchase intention with a significance value of 0.000 and a coefficient of determination of 92.2%. it can be concluded that product quality, price, and Instagram promotion together can increase consumer purchase intention toward Lafy products in Samarinda.